Checklist of the infraorder Tipulomorpha (Trichoceridae, Tipuloidea) (Diptera) of Finland - Salmela, Jukka; Petrašiūnas, Andrius (ZooKeys, 2014)
A checklist of the infraorder Tipulomorpha: families Trichoceridae, Pediciidae, Limoniidae, Cylindrotomidae and Tipulidae (Diptera) recorded from Finland.
Keywords: checklist; cylindrotomidae; diptera; Finland; limoniidae; pediciidae; tipulidae; trichoceridae